Fourth-Order Hankel Determinants and Toeplitz Determinants for Convex Functions Connected with Sine Functions - Farah Zulfiqar; Sarfraz Nawaz Malik; Mohsan Raza; Md. Shajib Ali (Journal of Mathematics)
This article deals with the upper bound of fourth-order Hankel and Toeplitz determinants for the convex functions which are defined by using the sine function. The main tools in this study are the coefficient inequalities for the class P of functions with positive real parts. Also, the investigation of the upper bound of the fourth-order Hankel determinant for 3-fold symmetric convex functions associated with the sine function is included.